PENAPISAN GALUR KEDELAI Glycine max (L.) Merrill TOLERAN TERHADAP NaCl UNTUK PENANAMAN DI LAHAN SALIN - Yuniati, Ratna (UI Scholars Hub, 2004)
Screening of Soybean Cultivars Glycine max (L.) Merrill under Sodium Chloride Stress Condition. Salinity is one of the most serious and widespread agricultural problems resulting in losses of yield. Generally, as land is more intensively cultivated, the salinity problem becomes more severe. A high concentration of NaCl greatly reduces growth of both the shoot and the root. One strategy available to cope with saline soil is to choose salt-tolerance crops or to select salt-tolerance cultivars within a crop. Experiments were conducted to asses the performance of ten cultivars soybean (Glycine max [L.] Merrill) to salt stress at germination and seedling stages. Salinity treatments were begun by adding 70, 80, 90, and 100 mM NaCl to the basal nutrient solution. According to germination percentage, fresh weight/dry weight ratios, and the percentage of dead apical buds we suggest that Wilis, Malabar and Sindoro were tolerant lines, Genjah Jepang, Lokan, and Tidar were moderate and the sensitive lines were Lumut, Yellow Biloxy, Si Cinang and Sriyono.